2011
DOI: 10.5152/akd.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coronary collateral circulation and plasma levels of N-terminal pro-B-type natriuretic peptide

Abstract: Objective: There have been numerous investigations demonstrating protective effects of awell-grown coronary collateral circulation (CCC) on left ventricular systolic function. N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) is released by ventricular myocardium as a result of increased myocardial wall stress. The aim of the study was to evaluate the relationship between CCC and plasma NT-pro-BNP levels. Methods: Study group was retrospectively selected from patients who had a coronary angiography at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Kadı et al, have found in a study including patients with totally occluded coronary arteries (however, if they are chronic is not emphasized) that well-developed CC could lower NT-proBNP levels via protecting from myocardial ischemia. 8 Another, more recent study investigating only CTO patients, showed that poor CC was associated with significantly higher NT-proBNP levels when compared with well-developed CC. 9 This result was explained by two mechanisms – firstly, by protection against myocardial ischemia provided by well-developed collaterals, and secondly, elevated NT-proBNP levels might be only reflection of the required humoral status for the stimulation of angiogenesis in patients with poor CC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadı et al, have found in a study including patients with totally occluded coronary arteries (however, if they are chronic is not emphasized) that well-developed CC could lower NT-proBNP levels via protecting from myocardial ischemia. 8 Another, more recent study investigating only CTO patients, showed that poor CC was associated with significantly higher NT-proBNP levels when compared with well-developed CC. 9 This result was explained by two mechanisms – firstly, by protection against myocardial ischemia provided by well-developed collaterals, and secondly, elevated NT-proBNP levels might be only reflection of the required humoral status for the stimulation of angiogenesis in patients with poor CC.…”
Section: Discussionmentioning
confidence: 99%
“… 7 There are conflicting data regarding effect of collaterals on natriuretic peptide levels. 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the increased wall tension in the group with poor left ventricle, as it has been shown in many studies that NT-proBNP levels increase, particularly as myocardial tension increases. [20,21] Considering the effects of the APJ system on angiogenesis and the regulatory roles of ELA protein in the cardiovascular system, it is reasonable to associate it with the formation of coronary collaterals. In this context, the presence of both APJ receptors and ELA protein in vascular smooth muscle cells and endothelium is strong evidence supporting this inference.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the presence of both APJ receptors and ELA protein in vascular smooth muscle cells and endothelium is strong evidence supporting this inference. [19][20][21] On the other hand, the mechanisms of these effects of ELA are also clear. Namely, ELA is thought to be important for heart formation and migration of cardiac progenitor cells for heart development during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation